Overprotective Parents: Its Impact on Self-Adjustment and Social Interaction - Anisa Mutiara Zain; Hardani Widhiastuti; Margaretha Maria Shinta Pratiwi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Adolescence is a developmental stage marked by rapid changes in emotional and social aspects, where parental roles play a significant influence. Overprotective parenting, though based on affection, can hinder adolescents’ autonomy and social competence. This study aimed to examine the influence of overprotective parenting on self-adjustment and social interaction abilities among 8th-grade students at SMP X in Bandar Lampung. Using a quantitative descriptive–correlational design, all 79 students were selected through total sampling. Data were collected using Likert-scale instruments measuring parental overprotection, self-adjustment, and social interaction, and analyzed using Pearson correlation and linear regression via SPSS 25. The findings showed that most students were in the moderate category for all variables, and the correlation between overprotective parenting and both self-adjustment and social interaction was negative but not significant (r < 0.1; p > 0.05). These results imply that parental overprotection alone does not substantially determine adolescents’ adaptability or social competence. Therefore, parents and schools are encouraged to implement balanced guidance strategies that foster independence and healthy social development among adolescents.Masa remaja merupakan tahap perkembangan yang ditandai dengan perubahan pesat pada aspek emosional dan sosial, di mana peran orang tua memiliki pengaruh yang besar. Pola asuh overprotective, meskipun dilandasi kasih sayang, dapat menghambat kemandirian dan kemampuan sosial remaja. Penelitian ini bertujuan untuk menguji pengaruh sikap overprotective orang tua terhadap penyesuaian diri dan kemampuan interaksi sosial siswa kelas 8 di SMP X Bandar Lampung. Metode penelitian menggunakan pendekatan kuantitatif deskriptif-korelasional dengan total sampling pada 79 siswa. Data dikumpulkan melalui skala Likert yang mengukur sikap overprotective, penyesuaian diri, dan interaksi sosial, kemudian dianalisis dengan uji korelasi Pearson dan regresi linear menggunakan SPSS 25. Hasil penelitian menunjukkan bahwa sebagian besar siswa berada pada kategori sedang untuk ketiga variabel, serta hubungan antara sikap overprotective dengan penyesuaian diri maupun interaksi sosial bersifat negatif namun tidak signifikan (r < 0,1; p > 0,05). Implikasi dari penelitian ini menekankan pentingnya pola asuh yang seimbang antara kontrol dan kebebasan, agar orang tua dan sekolah dapat bersama-sama mendukung perkembangan sosial dan kemandirian remaja secara optimal.